Strengthening the Role of Prospective Teachers as Agents of Resilience and Innovation through Disaster Preparedness Education and Digital Entrepreneurship Mentoring for PPG Students at IPI Garut - Yaman Suryaman; Galih Abdul Fatah Maulani; Nizar Alam Hamdani (Fakultas Kewirausahaan Universitas Garut, 2026)
Garut Regency faces a high risk of natural disasters amidst a rapidly evolving digital era that demands continuous innovation; consequently, this community service initiative was designed to strengthen the capacity of Teacher Professional Education (PPG) students at the Institute of Education Indonesia (IPI) Garut to act as dual agents resilient in the face of disasters and skilled in digital innovation. The implementation strategy encompassed disaster preparedness training utilizing an